1994
DOI: 10.1155/mbd.1994.512
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics and Mechanism of the Reaction Between Serum Albuminand Auranofin (and its Isopropyl Analogue) In Vitro

Abstract: The first detailed kinetic study of in vitro reactions between serum albumin and the secondgeneration gold drug Auranofin [Et3PAuSATg triethylphosphine-(2,3,4,6-tetra-O-acetyl-l-8-Dglucopytanosato-S-) gold(I)] and its tri-i-propylphosphine analogue, .iPr3PAuSATg, are reported. The reactions were investigated using Penefsky spun columns and NMR saturation transfer kinetics. Based on the Penefsky column data, the binding of the Et3PAuSATg to AIbSH (0.600 mM) was complete when gold concentrations were limiting: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…There are antiarthritic drugs like auranofin (Et 3 PAu‐ S ‐actylthioglucose), which are based on compounds containing gold(I) complexes and a thiol moiety. Cys34 is the principal binding site of auranofin on albumin and different adducts have been found ( Coffer et al ., 1987 ; Shaw, 1989 ; Dhubhghaill et al ., 1992 ; Roberts et al ., 1996 ). A complex series of reactions is involved in the albumin binding of this group of compounds to HMA and HNA ( Shaw, 1989 ; Roberts et al ., 1996 ) including ligand exchange and liberation of acetylthioglucose, which may in turn modify the redox situation on Cys34.…”
Section: Binding Properties and Oxidation Of Albuminmentioning
confidence: 99%
“…There are antiarthritic drugs like auranofin (Et 3 PAu‐ S ‐actylthioglucose), which are based on compounds containing gold(I) complexes and a thiol moiety. Cys34 is the principal binding site of auranofin on albumin and different adducts have been found ( Coffer et al ., 1987 ; Shaw, 1989 ; Dhubhghaill et al ., 1992 ; Roberts et al ., 1996 ). A complex series of reactions is involved in the albumin binding of this group of compounds to HMA and HNA ( Shaw, 1989 ; Roberts et al ., 1996 ) including ligand exchange and liberation of acetylthioglucose, which may in turn modify the redox situation on Cys34.…”
Section: Binding Properties and Oxidation Of Albuminmentioning
confidence: 99%
“…Thus, the state of Cys34 is an important origin for heterogeneity in albumin. There has been much interest in the Cys34 site, because not only does it act as a physiological antioxidant [5,6], but also as a binding site for a wide variety of biologically and clinically important small molecules, such as gold(I) antiarthritic drugs [7,8], platinum(II) anticancer drugs [9,10], mercurials [11], as well as a variety of drugs which bind as mixed disulfides, including captopril (an antihypertensive) [12] and disulfiram (an alcohol‐abuse drug) [13]. Importantly, 82% of nitric oxide in blood (≈ 7 µ m ) is transported as an S ‐nitrosothiol at Cys34 [14].…”
mentioning
confidence: 99%
“…180 Therefore, based on MS and 1 H NMR evidence, it was concluded that Cys34 was the first residue to interact with the Au I (PEt 3 ) + fragment. [180][181][182] Auration of Cys34 has been recently reported by X-ray crystallography, 183 as well as further evidence of the affinity of Auranofin toward thiols. 184,185 Docking studies, integrating spectroscopic/spectrometric data, allow the confirmation of this binding with F max = 41.8 (Fig.…”
Section: Generalization To Other Mcsmentioning
confidence: 71%